Design of a Mobile-Based Attendance System Integrated with Android-Based Geolocator - Aidil Akbar Simatupang; Alfian Maulana (CV. Multimedia Teknologi Kreatif, 2025)
The development of information technology has significantly impacted various aspects of life, including employee attendance administration. This study aims to design a mobile-based attendance system integrated with geolocation on Android devices to enhance the efficiency and accuracy of attendance recording. The system utilizes geolocation technology to validate user locations in real-time, reduce data manipulation, and improve employee accountability. The system was developed using the System Development Life Cycle (SDLC) approach with the Waterfall model, which includes analysis, design, implementation, and testing using the Black-box method. Testing results indicate that all features—such as login, attendance recording, profile management, employee addition, and location validation—function as specified. The implementation of this system offers a modern solution for more transparent and effective attendance management. These findings are expected to serve as a reference for organizations seeking to adopt reliable digital attendance systems aligned with the demands of the information technology era. Future research is recommended to develop additional features such as facial recognition or integration with performance management systems